A case of metastatic pancreatic adenocarcinoma with prolonged survival after combination of neoadjuvant FOLFIRINOX therapy and synchronous distal pancreatectomy and hepatectomy. Issue 6 (29th December 2014) - Neofytou, Kyriakos; Giakoustidis, Alexandros; Smyth, Elizabeth C.; Cunningham, David; Mudan, Satvinder
Abstract : In this case report we detail the treatment of a patient with pancreatic ductal adenocarcinoma and a solitary liver metastasis who received nine cycles of FOLFIRINOX therapy with favourable response. The patient subsequently underwent synchronous distal pancreatectomy and hepatectomy with an R0 resection followed by three further cycles of FOLFIRINOX. At the last follow‐up, 2 years from operation and 28 months from the diagnosis of metastatic pancreatic adenocarcinoma the patient remains disease free. J. Surg. Oncol. 2015 111:768–770 . © 2014 Wiley Periodicals, Inc.